THE IMPACT OF INTERMITTENT FASTING ON CARDIOVASCULAR HEALTH IN YOUNG ADULTS - Mohd. Ahmad, Ashutosh Jain, Manila Jain (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Cardiovascular disease (CVD) is the leading cause of global mortality,particularly burdening low- and middle-income countries like India. Rising rates of obesity,diabetes, and sedentary lifestyles significantly contribute to this trend. Intermittent fasting (IF),a time-restricted eating pattern